2000
DOI: 10.1002/(sici)1097-4636(200008)51:2<164::aid-jbm4>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Photoencapsulation of chondrocytes in poly(ethylene oxide)-based semi-interpenetrating networks

Abstract: A photopolymerizing hydrogel system provides an efficient method to encapsulate cells. The present work describes the in vitro analysis of bovine and ovine chondrocytes encapsulated in a poly(ethylene oxide)-dimethacrylate and poly(ethylene glycol) semi-interpenetrating network using a photopolymerization process. One day after encapsulation, (3-[4,5-dimethylthiazol-2-y1]-2, 5-diphenyl-2H-tetrazolium bromide) (MTT) and light microscopy showed chondrocyte survival and a dispersed cell population composed of ovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
167
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(172 citation statements)
references
References 16 publications
5
167
0
Order By: Relevance
“…The degradation of PEGDA was not determined, but literature values indicate a slow degradation rate. [90] Scaffold Microfabrication Using 2PP…”
Section: Synthesis and Characterization Of Photopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of PEGDA was not determined, but literature values indicate a slow degradation rate. [90] Scaffold Microfabrication Using 2PP…”
Section: Synthesis and Characterization Of Photopolymersmentioning
confidence: 99%
“…PEGDA is widely used in biomaterials and serves as a standard because of its good availability and biological inertness. [90] Although the cubic lattice is suitable for producing large volume scaffolds in a relatively short processing time, it is not optimal from the secundam-naturam paradigm: straight edges, acute angles, sharp turns and inhomogeneous curvature distribution along the scaffold surface are contra-naturam and should be prevented in biomorphic cell supports. A biomorphic geometry that mimics the secundam-naturam substrate and that is continuous through all space is the Schwarz primitive (P) minimal surface.…”
Section: Synthesis and Characterization Of Photopolymersmentioning
confidence: 99%
“…This was accomplished by pooling a solution of PEG-diacrylate:2,2-dimethoxy-2-phenyl-acetophenone (99.7:0.3, w/w) on the rubber casting of the TiN-modified silicon-patterned substrate. The replicated structures composed were shown to be biocompatible and non-adhesive to protein and cells [65,66]. Moreover, by slightly altering the method these authors showed that they could fabricate a high aspect ratio (b 5) microarray of microcups composed of the same biocompatible material [67].…”
Section: Microfluidicsmentioning
confidence: 99%
“…More sophisticated methods incorporate self-degradation of the matrices for later retransplantation of the in vitro expanded cells based upon a polyglycolic acid non-woven mesh with fibrin gel matrix assistance [1]. Photochemical matrix formation approaches have also been assessed for purposes of chondrocyte immobilisation, although significant cell losses have been observed using these techniques [17].…”
Section: Microencapsulation Of Chondrocytesmentioning
confidence: 99%